Correlation of MRI-derived adipose tissue measurements and anthropometric markers with prevalent hypertension in the community - Lorbeer, Roberto; Schlett, Christopher L. (Journal of hypertension, 2018)
Objectives: To compare the correlations of MRI-derived adipose tissue measurements and anthropometric markers, respectively, with prevalent hypertension in a community-based sample, free of clinical cardiovascular disease. - Methods: MRI-derived adipose tissue measurements were obtained in 345 participants (143 women; age 39-73 years) of the KORA FF4 survey from Southern Germany using a 3-Tesla machine and included total adipose tissue (TAT), visceral adipose tissue (VAT), subcutaneous adipose tissue (SCAT), hepatic fat fraction (HFF), pancreatic fat fraction (PFF) as well as pericardial adipose tissue (PAT). In addition, the anthropometric markers body mass index, waist circumference, hip circumference, waist-hip ratio (WHR) and waist-height ratio (WHtR) as well as blood pressure measurements were obtained. - Results: The prevalence of hypertension was 33.6% (women: 28%, men: 38%). VAT and PAT had the highest area under the curve (AUC) values for identifying individuals with prevalent hypertension (AUC: 0.75; 0.73, respectively), whereas WHtR and waist circumference were best performing anthropometric markers (AUC: 0.72; 0.70, respectively). A 1SD increment of TAT was associated with the highest odd for hypertension in the age-adjusted and sex-adjusted model (OR = 2.20, 95% CI 1.67-2.91, P < 0.001) and in the fully adjusted model (OR = 1.97, 95% CI 1.45-2.66, P < 0.001). TAT was the only MRI-derived adipose tissue measurement that was associated with hypertension independently of the best performing anthropometric marker waist circumference in the fully adjusted model (OR = 1.93, 95% CI 1.00-3.72, P = 0.049). - Conclusion: MRI-derived adipose tissue measurements perform similarly in identifying prevalent hypertension compared with anthropometric markers. Especially, TAT, VAT and PAT as well as WHtR and waist circumference were highly correlated with prevalent hypertension.
Gesehen am 10.07.2019